The role of nursing staff in the nutritional therapy of a child with cystic fibrosis - Czerwińska Pawluk, Iwona; Pawluk, Elwira Paula; Szymaszek, Angelo Daniel; Zukow, Walery (Journal of Education, Health and Sport, 2019)
Cystic fibrosis (CF) is classified as a rare genetic disease and at the same time is the most common inherited disease in an autosomal recessive way. In Poland the disease is diagnosed in 1 in 4394-5000 live neonatal births [7, 9]. CF is a systemic chronic disease with progressive progression, incurable [10]. The cause of most problems in patients with CF are: chronic obstructive lesions and respiratory tract infections and impaired digestion processes with their consequences. The basis in the patient care of CF is the education of the patient/his caregivers in the prevention and treatment of bronchopulmonary disease and modified nutrition rules.